Pemrosesan Query dan Pemeringkatan Hasil dalam Information Retrieval: Sebuah Kajian Literatur - Roberto Kaban; Poltak Sihombing; Mahdianta Pandia; Purwanto Simamora (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In this study, we reviewed the literature on information retrieval starting from the basics of Information Retrieval (IR), components and future challenges. The purpose of this study is to observe techniques that have been used by previous researchers in IR, especially query processing and ranking of search results. We used a literature review method by identifying, reviewing, and observing techniques in IR based on the results of several previous studies. We collected more literature sources from the ACM Digital Library, Researchgate and MDPI. From this research, we found several IR models for searching relevant documents (information) and ranking accurate results, including EXplanaTion RAnking (EXTRA), Deep-QPP, ColBERT-PRF and UQSCM-RFD.